KOREKSI BIAS BETA SAHAM DI BURSA EFEK INDONESIA PERIODE 2009-2012 - Indah Saptorini; Fifi Swandari (Universitas Lambung Mangkurat, 2013)
This study aims to determine whether the beta value of shares listed on the Indonesia Stock Exchange (BEI) is a bias beta due to nonsynchronous trading activities. There are 310 companies listed on the Stock Exchange 2009-2012 period sampled in this study. The bias needs to be corrected. From three methods employed : the Scholes and Williams (1977), the Dimson (1979), and the Fowler and Rorke (1983). Results of the analysis conclude that the shares on the Stock Exchange has a bias beta caused by not having a securities trading for some time. This resulted in the calculation of IHSG the period of t was biased because it uses the closing price of the period t-1. In this study bias beta correction method Scholes and Williams (1977), both one lag one lead and two lag two lead are better than the bias beta correction method Dimson (1979) and the bias beta correction method Fowler and Rorke (1983) because the value of beta Scholes and Williams after corrected close to one.